Endothelial IGF-1/IGF-1R signaling supports young-blood-induced restoration of blood–brain barrier integrity and microvascular architecture in aged mice: evidence from the heterochronic parabiosis model - Rafal Gulej; Rebeka Kristof; Roland Patai; Siva Sai Chandragiri; Shoba Ekambaram; Mark Nagykaldi; Evelyn Brunner; Peter Mukli; Adam Nyul-Toth; Dorina Nagy; Kiana Vali Kordestan; Raghavendra Yelahanka Nagaraja; et al. (GeroScience, 2026)
Aging is associated with blood–brain barrier (BBB) breakdown and microvascular rarefaction, key contributors to cerebral neuroinflammation, hypoperfusion, and vascular cognitive impairment and dementia (VCID). Exposure to a young systemic milieu through heterochronic parabiosis has been shown to restore BBB integrity and enhance cerebrovascular function in aged mice, suggesting that circulating factors can rejuvenate the aging brain. However, the molecular mediators responsible for these effects remain poorly defined. Circulating insulin-like growth factor-1 (IGF-1) declines markedly with age and has been implicated in endothelial dysfunction and BBB disruption, raising the possibility that IGF-1/IGF-1 receptor (IGF-1R) signaling contributes to the vascular rejuvenation induced by young blood. To test this hypothesis, we combined heterochronic parabiosis with complementary transgenic approaches targeting either endothelial IGF-1R deletion (VE-Cadherin-CreERT2/Igf1rfl/fl) or systemic IGF-1 knockdown (TBG-Cre-AAV8/Igf1fl/fl). BBB permeability to fluorescent tracers and cortical microvascular density were quantified by intravital two-photon microscopy through chronic cranial windows. We found that exposure of aged mice to young circulation markedly reduced BBB leakage and increased cortical capillary density. These beneficial effects were significantly attenuated in aged parabionts lacking endothelial IGF-1R or paired with young partners deficient in systemic IGF-1, demonstrating that both endothelial receptor activation and circulating IGF-1 availability are required for full cerebrovascular rejuvenation. Despite this attenuation, partial improvement persisted, indicating that IGF-1/IGF-1R signaling contributes to, but does not fully account for, the vascular benefits of young blood. These findings identify the IGF-1/IGF-1R axis as an important mediator of young blood–induced restoration of BBB integrity and microvascular density. Targeting downstream effectors of IGF-1R signaling, together with lifestyle interventions that enhance somatotropic axis responsiveness, may offer geroscience-guided strategies to preserve BBB function and cognitive resilience in aging.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Developing topsoil structure through conservation management to protect subsoil from compaction - Gunther Liebhard; Marton Toth; Christine Stumpp; Gernot Bodner; Andreas Klik; Xiaoping Zhang; Stefan Strohmeier; Peter Strauss (Soil and Tillage Research, 2025)

Mortality, functional outcome, and bleeding risk after early versus delayed thrombectomy - Zoltan Ungvari; János Tibor Fekete; Mónika Fekete; Andrea Lehoczki; Rafal Gulej; Farzaneh Sorond; Eric Liotta; Calin I. Prodan; Peter Toth; Csaba Kiss; Anna Ungvari; Balázs Győrffy (GeroScience, 2025)
Endovascular thrombectomy (EVT) is an established treatment for acute ischemic stroke, due to large vessel occlusion (LVO), but the optimal time window for intervention remains a subject of ongoing debate. We aimed to assess the impact of treatment timing on mortality, functional outcomes, and safety by comparing early (≤ 6 h) versus late (> 6–24 h) EVT. We conducted a systematic review and meta-analysis to evaluate the effect of time to intervention on outcomes of endovascular thrombectomy (EVT) in acute ischemic stroke. Four databases (PubMed, Web of Science, Cochrane Library, and EMBASE) were searched for studies published between 2000 and 2024. Eligible randomized controlled trials and cohort studies reported on 90-day mortality, functional outcome (modified Rankin Scale, mRS), or symptomatic intracranial hemorrhage (sICH), stratified by treatment timing (≤ 6 h vs. > 6–24 h from symptom onset). Pooled incidence rates, incidence rate differences (IRD), and incidence rate ratios (IRR) were calculated using random-effects models. Eighteen studies met inclusion criteria. The pooled incidence of symptomatic intracranial hemorrhage (sICH) was 0.19 events per person-year (95% CI: 0.12–0.26) in the early group and 0.23 events per person-year (95% CI: 0.11–0.35) in the late group, with no significant difference between groups (incidence rate difference [IRD] − 0.028; p = 0.33, incidence rate ratio [IRR] 0.88; p = 0.33). For mortality, early EVT showed a significantly lower incidence rate of 0.66 events per person-year (95% CI: 0.51–0.82) compared to 0.77 events per person-year (95% CI: 0.63–0.91) in the late EVT group (IRD − 0.148; p = 0.0012, IRR 0.81; p = 0.0014). Functional independence was more frequent in the early group (1.72; 95% CI: 1.42–2.01) than in the late group (1.45; 95% CI: 0.91–1.98) (IRD 0.32; p < 0.0001, IRR 1.22; p < 0.0001). Heterogeneity was moderate to high across outcomes. The timing of endovascular thrombectomy significantly influences clinical outcomes in acute ischemic stroke. Our analysis shows that early intervention (within 6 h) is associated with a significantly lower mortality rate and a higher likelihood of achieving functional independence at 90 days compared to late intervention (beyond 6 up to 24 h). The incidence of symptomatic intracranial hemorrhage did not differ significantly between the groups, suggesting that late treatment does not increase safety risks. These findings underscore the importance of minimizing treatment delays, while also supporting the continued use of EVT in selected patients beyond the 6-h window.

Age-related and dual task-induced gait alterations and asymmetry: optimizing the Semmelweis Study gait assessment protocol - Peter Mukli; Mihaly Muranyi; Ágnes Lipecz; Zsofia Szarvas; Tamás Csípő; Anna Ungvari; Mónika Fekete; Vince Fazekas-Pongor; Anna Peterfi; Ágnes Fehér; Norbert Dosa; Noémi Mózes; et al. (GeroScience, 2025)
Gait alterations are recognized as early markers of age-related decline and cognitive impairment. Dual-task assessments, which impose cognitive load while walking, provide valuable insights into gait control limitations and cognitive-motor interactions in aging populations. This study evaluates age-related and cognitive load-induced changes in gait parameters, with a particular focus on asymmetry, and aims to optimize the gait assessment protocol for the Semmelweis Study framework. The Semmelweis Study is a large-scale workplace cohort investigating the determinants of unhealthy aging and promoting healthy brain aging by identifying risk factors and protective mechanisms influencing vascular, metabolic, and neurocognitive decline. As part of this initiative, gait analysis is emerging as a critical tool for assessing functional aging, detecting early signs of mobility and cognitive impairment, and contributing to biological age assessment. A cross-sectional analysis was conducted on adults aged 23 to 87 years using a pressure-sensitive walkway system. Participants were evaluated under single-task conditions (normal walking) and dual-task conditions (walking while performing a concurrent cognitive task). Spatiotemporal gait parameters, asymmetry indices, and dual-task costs were analyzed to assess age-related changes in gait performance and cognitive-motor interactions. Aging was associated with significant reductions in gait speed, step length, and stride length, along with a corresponding increase in gait asymmetry. Dual-task conditions exacerbated these alterations, indicating age-related impairments in cognitive-motor integration. Asymmetry indices were sensitive to aging effects, suggesting their potential as biomarkers for functional decline. The dual-task cost on gait was significantly greater in older adults, reinforcing the interplay between cognitive and motor systems in aging. Age-related gait alterations, particularly under cognitive load, underscore the importance of comprehensive gait assessments in aging research. Our findings contribute to the optimization of the Semmelweis Study gait assessment protocol by identifying key gait parameters that capture functional decline and biological aging. Integrating dual-task gait analysis into large-scale epidemiological studies has the potential to enhance early detection of brain health decline, refine biological age estimation, and guide targeted interventions to support healthy aging and neuromotor resilience.

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Chronic impairment of neurovascular coupling and cognitive decline in young survivors of severe traumatic brain injury - Zsofia Dina Magyar-Sumegi; Mark Csendes; Dominika Lendvai-Emmert; Gabriella Sebestyen; Viktoria Tamas; Szabolcs Bandi; Andras Czigler; Andriy Yabluchanskiy; Stefano Tarantini; Zoltan Ungvari; Endre Czeiter; Krisztina Amrein; et al. (GeroScience, 2025)
Severe traumatic brain injury (TBI) leads to chronic cognitive decline, imposing a significant societal burden. The regulation of cerebral blood flow (CBF) is critical for cognitive function, and acute disruptions in CBF regulation predict poor TBI outcomes. However, the long-term effects of TBI on CBF regulation and their association with cognitive function remain poorly understood. This study aimed to investigate whether severe TBI results in chronic CBF dysregulation and whether this contributes to long-term cognitive deficits. Additionally, we examined the role of TBI-induced insulin-like growth factor 1 (IGF-1) deficiency in cerebrovascular dysfunction. We assessed cognitive function, basal CBF (via phase contrast MRI), CBF autoregulation (via transcranial Doppler), and neurovascular coupling (NVC) in 33 TBI survivors (mean age 37.6 years, ~ 10 years post-injury) and 21 age-matched healthy controls. Serum IGF-1 levels were also measured. TBI survivors exhibited significant impairments in memory and executive function compared to controls. While basal CBF and autoregulation remained intact, NVC responses were chronically impaired and correlated with cognitive deficits. However, IGF-1 levels did not differ between groups and were not associated with NVC impairment or cognitive function. Our findings indicate that severe TBI results in chronic impairment of neurovascular coupling, which likely contributes to long-term cognitive deficits. These results highlight the need for further research to identify underlying neurovascular mechanisms and develop interventions to restore NVC and cognitive function in TBI survivors.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Functional ultrasound imaging reveals microvascular rarefaction, decreased cerebral blood flow, and impaired neurovascular coupling in a mouse model of paclitaxel-induced chemobrain - Siva Sai Chandragiri; Adam Nyul-Toth; Sharon Negri; Roland Patai; Rafal Gulej; Boglarka Csik; Santny Shanmugarama; Kiana Vali Kordestan; Mark Nagykaldi; Peter Mukli; Anna Ungvari; Andriy Yabluchanskiy; et al. (GeroScience, 2025)
Chemotherapy-induced cognitive impairment (CICI), often referred to as “chemobrain,” significantly affects the quality of life in cancer survivors. Although traditionally attributed to neuronal toxicity, emerging evidence suggests a key role of cerebrovascular dysfunction in its pathogenesis. We hypothesized that paclitaxel (PTX, Taxol) treatment induces long-term cerebrovascular dysfunction, including microvascular rarefaction, impaired neurovascular coupling (NVC), and altered cerebral blood flow (CBF), which contribute to CICI. Using a clinically relevant PTX treatment regimen in non-tumor-bearing mice, we evaluated the long-term effects of PTX on cerebrovascular health. Ultrasound localization microscopy (ULM) and functional ultrasound imaging (fUS) were employed to assess microvascular density, CBF, and NVC. PTX treatment resulted in a significant reduction in microvascular density in the cerebral cortex and hippocampus, key regions involved in cognitive function. PTX significantly reduced blood velocity in the middle cerebral artery. Moreover, PTX impaired NVC responses, as evidenced by a diminished CBF increase in response to whisker stimulation, indicative of impaired reactive hyperemia. In conclusion, these findings demonstrate that PTX induces long-lasting cerebrovascular dysfunction, including microvascular rarefaction, impaired NVC, and altered CBF dynamics, which likely contribute to CICI. This study underscores the critical role of cerebrovascular health in cognitive function and highlights the potential of targeting cerebrovascular pathways as a therapeutic approach for mitigating chemotherapy-induced cognitive deficits.

Persisting blood–brain barrier disruption following cisplatin treatment in a mouse model of chemotherapy-associated cognitive impairment - Roland Patai; Boglarka Csik; Adam Nyul-Toth; Rafal Gulej; Kiana Vali Kordestan; Siva Sai Chandragiri; Santny Shanmugarama; Stefano Tarantini; Peter Mukli; Anna Ungvari; Andriy Yabluchanskiy; Zoltan Ungvari; et al. (GeroScience, 2025)
Chemotherapy-related cognitive impairment, commonly referred to as “chemobrain,” significantly affects cancer survivors’ quality of life, yet its underlying mechanisms remain unclear. Most chemotherapeutic agents cannot cross the blood–brain barrier (BBB), yet they cause central nervous system side effects, suggesting alternative pathways of toxicity. Given that these drugs interact with the cerebrovascular endothelium at their highest concentrations, it is logical to hypothesize that endothelial damage contributes to these effects. Our recent studies demonstrated that paclitaxel-induced cognitive impairment in a mouse model results in a partial BBB disruption and subsequent neuroinflammation, mediated by chemotherapy-induced endothelial senescence. In this pilot study, we used two-photon microscopy to assess BBB permeability in mice receiving a clinically relevant cisplatin regimen, evaluating the leakage of fluorescent dextran tracers of varying molecular weights. Two months post-treatment, cisplatin-treated mice exhibited significantly increased BBB permeability to smaller molecular tracers (40 kDa, 3 kDa, and 0.3 kDa) compared to controls, indicating sustained BBB disruption. These results align with our findings for paclitaxel and suggest that chemotherapy-induced endothelial damage and senescence play a central role in cognitive impairments. Interventions targeting endothelial health could mitigate these long-term effects, improving cognitive outcomes for cancer survivors.

Cisplatin and methotrexate induce brain microvascular endothelial and microglial senescence in mouse models of chemotherapy-associated cognitive impairment - Boglarka Csik; Kiana Vali Kordestan; Rafal Gulej; Roland Patai; Adam Nyul-Toth; Santny Shanmugarama; Peter Mukli; Anna Ungvari; Karl E. Balsara; Rene Y. McNall; Talayeh Razzaghi; Stefano Tarantini; et al. (GeroScience, 2025)
The increasing number of cancer survivors has brought heightened attention to the side effects of cancer therapies, including chemotherapy-related cognitive impairment (CRCI, commonly referred to as “chemobrain”). Cisplatin and methotrexate, commonly used first-line chemotherapeutics in gynecologic oncology for cancers such as breast, ovarian, and bladder cancer, are clinically associated with long-term cognitive deficits. Building on our previous preclinical studies demonstrating that paclitaxel chemotherapy induces cerebrovascular endothelial and microglial senescence—leading to blood–brain barrier (BBB) disruption, neuroinflammation, and cognitive impairments—we hypothesized that cisplatin and methotrexate might similarly promote senescence in these cells. Senescent endothelial cells and microglia are known to contribute to neuroinflammation, cerebral blood flow dysregulation, and white matter damage, exacerbating cognitive decline. Using the p16-3MR mouse model, which expresses red fluorescent protein (RFP) in p16 + senescent cells, we evaluated the impact of these drugs on brain endothelial and microglial senescence through flow cytometry. Our results show a significant increase in senescent endothelial and microglial cells two months post-treatment with cisplatin or methotrexate compared to controls. These findings offer new insights into the shared mechanisms underlying CRCI associated with cisplatin or methotrexate treatment, extending our understanding of chemotherapy-induced vascular cognitive impairments.

Transcriptomic profiling of senescence effects on blood–brain barrier-related gene expression in brain capillary endothelial cells in a mouse model of paclitaxel-induced chemobrain - Roland Patai; Tamas Kiss; Rafal Gulej; Adam Nyul-Toth; Boglarka Csik; Siva Sai Chandragiri; Santny Shanmugarama; Stefano Tarantini; Anna Ungvari; Pal Pacher; Peter Mukli; Andriy Yabluchanskiy; et al. (GeroScience, 2025)
Chemotherapy-induced cognitive impairment (CICI), commonly referred to as “chemobrain,” is a frequent and debilitating side effect experienced by cancer survivors treated with paclitaxel (PTX). Preclinical models have shown that PTX promotes cerebromicrovascular endothelial cell senescence, leading to chronic blood–brain barrier (BBB) disruption and neuroinflammation. Conversely, the elimination of senescent cells through senolytic therapies has been shown to restore BBB integrity, reduce neuroinflammation, and alleviate PTX-induced cognitive impairment. In this study, we tested the hypothesis that PTX-induced endothelial senescence alters gene expression patterns associated with BBB integrity. To investigate this, we analyzed a scRNA-seq dataset from the brains of mice treated with a clinically relevant PTX regimen alongside vehicle-treated control mice. We identified capillary endothelial cells by their distinct transcriptomic profiles and matched these profiles to known transcriptomic markers of cellular senescence. Our analysis confirmed that PTX induces senescence in capillary endothelial cells and revealed significant transcriptional alterations linked to impaired BBB function. In senescent endothelial cells, gene set enrichment analysis (GSEA) highlighted downregulated pathways associated with cell junction assembly and upregulated pathways involved in extracellular matrix remodeling and inflammatory signaling, including Vitronectin (VTN) and Pleiotrophin (PTN) pathways. Additionally, cell–cell communication analysis revealed reduced Junctional Adhesion Molecule (JAM) signaling, further implicating senescence in BBB disruption. These findings highlight endothelial senescence as a driver of BBB dysfunction through transcriptional changes and altered intercellular signaling. The enrichment of VTN and PTN pathways in the senescent state indicates a shift toward vascular remodeling and inflammation, exacerbating microvascular fragility and BBB disruption. Supported by prior experimental findings, this study suggests that targeting endothelial senescence and its downstream effects could mitigate PTX-induced BBB dysfunction and associated cognitive impairments. These results advance our understanding of CICI pathogenesis and provide a foundation for developing therapeutic strategies aimed at preserving vascular integrity.

The vasoprotective role of IGF-1 signaling in the cerebral microcirculation: prevention of cerebral microhemorrhages in aging - Levente Stankovics; Anna Ungvari; Mónika Fekete; Adam Nyul-Toth; Peter Mukli; Roland Patai; Boglarka Csik; Rafal Gulej; Shannon Conley; Anna Csiszar; Peter Toth (GeroScience, 2024)
Aging is closely associated with various cerebrovascular pathologies that significantly impact brain function, with cerebral small vessel disease (CSVD) being a major contributor to cognitive decline in the elderly. Consequences of CSVD include cerebral microhemorrhages (CMH), which are small intracerebral bleeds resulting from the rupture of microvessels. CMHs are prevalent in aging populations, affecting approximately 50% of individuals over 80, and are linked to increased risks of vascular cognitive impairment and dementia (VCID). Hypertension is a primary risk factor for CMHs. Vascular smooth muscle cells (VSMCs) adapt to hypertension by undergoing hypertrophy and producing extracellular matrix (ECM) components, which reinforce vessel walls. Myogenic autoregulation, which involves pressure-induced constriction, helps prevent excessive pressure from damaging the vulnerable microvasculature. However, aging impairs these adaptive mechanisms, weakening vessel walls and increasing susceptibility to damage. Insulin-like Growth Factor 1 (IGF-1) is crucial for vascular health, promoting VSMC hypertrophy, ECM production, and maintaining normal myogenic protection. IGF-1 also prevents microvascular senescence, reduces reactive oxygen species (ROS) production, and regulates matrix metalloproteinase (MMP) activity, which is vital for ECM remodeling and stabilization. IGF-1 deficiency, common in aging, compromises these protective mechanisms, increasing the risk of CMHs. This review explores the vasoprotective role of IGF-1 signaling in the cerebral microcirculation and its implications for preventing hypertension-induced CMHs in aging. Understanding and addressing the decline in IGF-1 signaling with age are crucial for maintaining cerebrovascular health and preventing hypertension-related vascular injuries in the aging population.

Long-term effects of tillage systems on soil health of a silt loam in Lower Austria - Marton Toth; Christine Stumpp; Andreas Klik; Peter Strauss; Bano Mehdi-Schulz; Gunther Liebhard; Stefan Strohmeier (Soil and Tillage Research, 2024)

Longitudinal detection of gait alterations associated with hypertension-induced cerebral microhemorrhages in mice: predictive role of stride length and stride time asymmetry and increased gait entropy - Zoltan Ungvari; Mihaly Muranyi; Rafal Gulej; Sharon Negri; Adam Nyul-Toth; Boglarka Csik; Roland Patai; Shannon Conley; Madison Milan; Jonathan Bagwell; Daniel O’Connor; Amber Tarantini; et al. (GeroScience, 2024)
Cerebral microhemorrhages (CMHs) are of paramount importance as they not only signify underlying vascular pathology but also have profound implications for cognitive function and neurological health, serving as a critical indicator for the early detection and management of vascular cognitive impairment (VCI). This study aimed to investigate the effects of hypertension-induced CMHs on gait dynamics in a mouse model, focusing on the utility of advanced gait metrics as sensitive indicators of subclinical neurological alterations associated with CMHs. To induce CMHs, we employed a hypertensive mouse model, using a combination of Angiotensin II and L-NAME to elevate blood pressure, further supplemented with phenylephrine to mimic transient blood pressure fluctuations. Gait dynamics were analyzed using the CatWalk system, with emphasis on symmetry indices for Stride Length (SL), Stride Time (ST), and paw print area, as well as measures of gait entropy and regularity. The study spanned a 30-day experimental period, capturing day-to-day variations in gait parameters to assess the impact of CMHs. Temporary surges in gait asymmetry, detected as deviations from median gait metrics, suggested the occurrence of subclinical neurological signs associated with approximately 50% of all histologically verified CMHs. Our findings also demonstrated that increases in gait entropy correlated with periods of increased gait asymmetry, providing insights into the complexity of gait dynamics in response to CMHs. Significant correlations were found between SL and ST symmetry indices and between these indices and the paw print area symmetry index post-hypertension induction, indicating the interdependence of spatial and temporal aspects of gait affected by CMHs. Collectively, advanced gait metrics revealed sensitive, dynamic alterations in gait regulation associated with CMHs, resembling the temporal characteristics of transient ischemic attacks (TIAs). This underscores their potential as non-invasive indicators of subclinical neurological impacts. This study supports the use of detailed gait analysis as a valuable tool for detecting subtle neurological changes, with implications for the early diagnosis and monitoring of cerebral small vessel disease (CSVD) in clinical settings.

Linking peripheral atherosclerosis to blood–brain barrier disruption: elucidating its role as a manifestation of cerebral small vessel disease in vascular cognitive impairment - Ádám Nyúl-Tóth; Roland Patai; Anna Csiszar; Anna Ungvari; Rafal Gulej; Peter Mukli; Andriy Yabluchanskiy; Zoltan Benyo; Peter Sotonyi; Calin I. Prodan; Eric M. Liotta; Peter Toth; et al. (GeroScience, 2024)
Aging plays a pivotal role in the pathogenesis of cerebral small vessel disease (CSVD), contributing to the onset and progression of vascular cognitive impairment and dementia (VCID). In older adults, CSVD often leads to significant pathological outcomes, including blood–brain barrier (BBB) disruption, which in turn triggers neuroinflammation and white matter damage. This damage is frequently observed as white matter hyperintensities (WMHs) in neuroimaging studies. There is mounting evidence that older adults with atherosclerotic vascular diseases, such as peripheral artery disease, ischemic heart disease, and carotid artery stenosis, face a heightened risk of developing CSVD and VCID. This review explores the complex relationship between peripheral atherosclerosis, the pathogenesis of CSVD, and BBB disruption. It explores the continuum of vascular aging, emphasizing the shared pathomechanisms that underlie atherosclerosis in large arteries and BBB disruption in the cerebral microcirculation, exacerbating both CSVD and VCID. By reviewing current evidence, this paper discusses the impact of endothelial dysfunction, cellular senescence, inflammation, and oxidative stress on vascular and neurovascular health. This review aims to enhance understanding of these complex interactions and advocate for integrated approaches to manage vascular health, thereby mitigating the risk and progression of CSVD and VCID.

Atherosclerotic burden and cerebral small vessel disease: exploring the link through microvascular aging and cerebral microhemorrhages - Anna Csiszar; Anna Ungvari; Roland Patai; Rafal Gulej; Andriy Yabluchanskiy; Zoltan Benyo; Illes Kovacs; Peter Sotonyi; Angelia C. Kirkpartrick; Calin I. Prodan; Eric M. Liotta; Xin A. Zhang; et al. (GeroScience, 2024)
Cerebral microhemorrhages (CMHs, also known as cerebral microbleeds) are a critical but frequently underestimated aspect of cerebral small vessel disease (CSVD), bearing substantial clinical consequences. Detectable through sensitive neuroimaging techniques, CMHs reveal an extensive pathological landscape. They are prevalent in the aging population, with multiple CMHs often being observed in a given individual. CMHs are closely associated with accelerated cognitive decline and are increasingly recognized as key contributors to the pathogenesis of vascular cognitive impairment and dementia (VCID) and Alzheimer’s disease (AD). This review paper delves into the hypothesis that atherosclerosis, a prevalent age-related large vessel disease, extends its pathological influence into the cerebral microcirculation, thereby contributing to the development and progression of CSVD, with a specific focus on CMHs. We explore the concept of vascular aging as a continuum, bridging macrovascular pathologies like atherosclerosis with microvascular abnormalities characteristic of CSVD. We posit that the same risk factors precipitating accelerated aging in large vessels (i.e., atherogenesis), primarily through oxidative stress and inflammatory pathways, similarly instigate accelerated microvascular aging. Accelerated microvascular aging leads to increased microvascular fragility, which in turn predisposes to the formation of CMHs. The presence of hypertension and amyloid pathology further intensifies this process. We comprehensively overview the current body of evidence supporting this interconnected vascular hypothesis. Our review includes an examination of epidemiological data, which provides insights into the prevalence and impact of CMHs in the context of atherosclerosis and CSVD. Furthermore, we explore the shared mechanisms between large vessel aging, atherogenesis, microvascular aging, and CSVD, particularly focusing on how these intertwined processes contribute to the genesis of CMHs. By highlighting the role of vascular aging in the pathophysiology of CMHs, this review seeks to enhance the understanding of CSVD and its links to systemic vascular disorders. Our aim is to provide insights that could inform future therapeutic approaches and research directions in the realm of neurovascular health.

Preventing spontaneous cerebral microhemorrhages in aging mice: a novel approach targeting cellular senescence with ABT263/navitoclax - Janet Faakye; Ádám Nyúl-Tóth; Mihaly Muranyi; Rafal Gulej; Boglarka Csik; Santny Shanmugarama; Stefano Tarantini; Sharon Negri; Calin Prodan; Peter Mukli; Andriy Yabluchanskiy; Shannon Conley; et al. (GeroScience, 2023)

Industry 4.0, multinationals, and sustainable development: A bibliometric analysis - José Dias Lopes; João Estevão; Agnes Toth-Peter (Journal of Cleaner Production, 2023)

Imaging the time course, morphology, neuronal tissue compression, and resolution of cerebral microhemorrhages in mice using intravital two-photon microscopy: insights into arteriolar, capillary, and venular origin - Janet Faakye; Ádám Nyúl-Tóth; Rafal Gulej; Boglarka Csik; Stefano Tarantini; Santny Shanmugarama; Calin Prodan; Peter Mukli; Andriy Yabluchanskiy; Shannon Conley; Peter Toth; Anna Csiszar; et al. (GeroScience, 2023)

DNA methylation clock DNAmFitAge shows regular exercise is associated with slower aging and systemic adaptation - Matyas Jokai; Ferenc Torma; Kristen M. McGreevy; Erika Koltai; Zoltan Bori; Gergely Babszki; Peter Bakonyi; Zoltan Gombos; Bernadett Gyorgy; Dora Aczel; Laszlo Toth; Peter Osvath; et al. (GeroScience, 2023)
DNAmPhenoAge, DNAmGrimAge, and the newly developed DNAmFitAge are DNA methylation (DNAm)-based biomarkers that reflect the individual aging process. Here, we examine the relationship between physical fitness and DNAm-based biomarkers in adults aged 33–88 with a wide range of physical fitness (including athletes with long-term training history). Higher levels of VO 2 max ( ρ = 0.2, p = 6.4E − 4, r = 0.19, p = 1.2E − 3), Jumpmax ( p = 0.11, p = 5.5E − 2, r = 0.13, p = 2.8E − 2), Gripmax ( ρ = 0.17, p = 3.5E − 3, r = 0.16, p = 5.6E − 3), and HDL levels ( ρ = 0.18, p = 1.95E − 3, r = 0.19, p = 1.1E − 3) are associated with better verbal short-term memory. In addition, verbal short-term memory is associated with decelerated aging assessed with the new DNAm biomarker FitAgeAcceleration ( ρ : − 0.18, p = 0.0017). DNAmFitAge can distinguish high-fitness individuals from low/medium-fitness individuals better than existing DNAm biomarkers and estimates a younger biological age in the high-fit males and females (1.5 and 2.0 years younger, respectively). Our research shows that regular physical exercise contributes to observable physiological and methylation differences which are beneficial to the aging process. DNAmFitAge has now emerged as a new biological marker of quality of life.

Recent advances in the delivery and applications of nonviral CRISPR/Cas9 gene editing - Frazer Sinclair; Anjuman A. Begum; Charles C. Dai; Istvan Toth; Peter M. Moyle (Drug Delivery and Translational Research, 2023)

Industry 4.0 as an enabler in transitioning to circular business models: A systematic literature review - Agnes Toth-Peter; Rui Torres de Oliveira; Shane Mathews; Leonie Barner; Sandra Figueira (Journal of Cleaner Production, 2023)

Age-related decline in circulating IGF-1 associates with impaired neurovascular coupling responses in older adults - Luca Toth; Andras Czigler; Emoke Hegedus; Hedvig Komaromy; Krisztina Amrein; Endre Czeiter; Andriy Yabluchanskiy; Akos Koller; Gergely Orsi; Gabor Perlaki; Attila Schwarcz; Andras Buki; et al. (GeroScience, 2022)
Impairment of moment-to-moment adjustment of cerebral blood flow (CBF) to the increased oxygen and energy requirements of active brain regions via neurovascular coupling (NVC) contributes to the genesis of age-related cognitive impairment. Aging is associated with marked deficiency in the vasoprotective hormone insulin-like growth factor-1 (IGF-1). Preclinical studies on animal models of aging suggest that circulating IGF-1 deficiency is causally linked to impairment of NVC responses. The present study was designed to test the hypotheses that decreases in circulating IGF-1 levels in older adults also predict the magnitude of age-related decline of NVC responses. In a single-center cross-sectional study, we enrolled healthy young ( n = 31, 11 female, 20 male, mean age: 28.4 + / − 4.2 years) and aged volunteers ( n = 32, 18 female, 14 male, mean age: 67.9 + / − 4.1 years). Serum IGF-1 level, basal CBF (phase contrast magnetic resonance imaging (MRI)), and NVC responses during the trail making task (with transcranial Doppler sonography) were assessed. We found that circulating IGF-1 levels were significantly decreased with age and associated with decreased basal CBF. Age-related decline in IGF-1 levels predicted the magnitude of age-related decline in NVC responses. In conclusion, our study provides additional evidence in support of the concept that age-related circulating IGF-1 deficiency contributes to neurovascular aging, impairing CBF and functional hyperemia in older adults.

A stochastic simulation model for assessing the masking effects of road noise for wildlife, outdoor recreation, and bioacoustic monitoring - Cory A. Toth; Benjamin P. Pauli; Christopher J. W. McClure; Clinton D. Francis; Peter Newman; Jesse R. Barber; Kurt Fristrup (Oecologia, 2022)
Traffic noise is one of the leading causes of reductions in animal abundances near roads. Acoustic masking of conspecific signals and adventitious cues is one mechanism that likely causes animals to abandon loud areas. However, masking effects can be difficult to document in situ and the effects of infrequent noise events may be impractical to study. Here, we present the Soundscapes model, a stochastic individual-based model that dynamically models the listening areas of animals searching for acoustic resources (“searchers"). The model also studies the masking effects of noise for human detections of the searchers. The model is set in a landscape adjacent to a road. Noise produced by vehicles traveling on that road is represented by calibrated spectra that vary with speed. Noise propagation is implemented using ISO-9613 procedures. We present demonstration simulations that quantify declines in searcher efficiency and human detection of searchers at relatively low traffic volumes, fewer than 50 vehicles per hour. Traffic noise is pervasive, and the Soundscapes model offers an extensible tool to study the effects of noise on bioacoustics monitoring, point-count surveys, the restorative value of natural soundscapes, and auditory performance in an ecological context.

Effects of pituitary adenylate cyclase activating polypeptide (PACAP) in corneal epithelial regeneration and signal transduction in rats - Peter Kiss; Jozsef Farkas; Krisztina Kovacs; Valeria Gaal; Zsolt Biro; Aliz Szabo; Tamas Atlasz; Inez Bosnyak; Gabor Toth; Andrea Tamas; Dora Reglodi (International Journal of Peptide Research and Therapeutics, 2022)
Corneal epithelium responds to insults with a rapid wound healing, which is essential for maintaining vision. The proper balance of apoptotic and proliferation-stimulating pathways is critical for normal regeneration. Pituitary adenylate cyclase activating polypeptide (PACAP) is an important growth factor during the development of the nervous system and exerts cytoprotective effects in injuries. The aim of the present study was to investigate the effects of PACAP on corneal epithelial wound healing in rats and on two important protective signaling molecules, Akt and ERK1/2, both of which have been reported to play important roles during cell survival and regeneration, including corneal wound healing. Wistar rats received PACAP treatment in form of eyedrops, containing 1, 5 and 10 µg PACAP27, immediately and every two hours after corneal abrasion. Corneas were stained with fluorescein dye and further processed for histological staining or Western blot analysis for Akt and ERK1/2 expression. Our results showed that topical PACAP application enhanced corneal wound healing, as the area of injury was significantly less in PACAP-treated groups. Furthermore, both ERK1/2 and Akt signaling was induced upon PACAP administration in both injured and intact corneas. In summary, the present results show that PACAP enhances corneal wound healing in a rat model of corneal abrasion.

Cerebral venous congestion exacerbates cerebral microhemorrhages in mice - Adam Nyul-Toth; Gabor A. Fulop; Stefano Tarantini; Tamas Kiss; Chetan Ahire; Janet A. Faakye; Anna Ungvari; Peter Toth; Attila Toth; Anna Csiszar; Zoltan Ungvari (GeroScience, 2022)

Treatment with the BCL-2/BCL-xL inhibitor senolytic drug ABT263/Navitoclax improves functional hyperemia in aged mice - Stefano Tarantini; Priya Balasubramanian; Jordan Delfavero; Tamas Csipo; Andriy Yabluchanskiy; Tamas Kiss; Ádám Nyúl-Tóth; Peter Mukli; Peter Toth; Chetan Ahire; Anna Ungvari; Zoltan Benyo; et al. (GeroScience, 2021)

Endothelial deficiency of insulin-like growth factor-1 receptor (IGF1R) impairs neurovascular coupling responses in mice, mimicking aspects of the brain aging phenotype - Stefano Tarantini; Ádám Nyúl-Tóth; Andriy Yabluchanskiy; Tamas Csipo; Peter Mukli; Priya Balasubramanian; Anna Ungvari; Peter Toth; Zoltan Benyo; William E. Sonntag; Zoltan Ungvari; Anna Csiszar (GeroScience, 2021)

Early manifestation of gait alterations in the Tg2576 mouse model of Alzheimer’s disease - Adam Nyul-Toth; Jordan DelFavero; Peter Mukli; Amber Tarantini; Anna Ungvari; Andriy Yabluchanskiy; Anna Csiszar; Zoltan Ungvari; Stefano Tarantini (GeroScience, 2021)

Agroforestry contributions to smallholder farmer food security in Indonesia - Colm Duffy; Gregory G. Toth; Robert P. O. Hagan; Peter C. McKeown; Syed Ajijur Rahman; Yekti Widyaningsih; Terry C. H. Sunderland; Charles Spillane (Agroforestry Systems, 2021)
Agroforestry has potential for strengthening the climate change resilience of smallholder farmers in Southeast Asia. In Indonesia, the food security challenges faced by smallholders will likely worsen due to climate change impacts. Agroforestry provides and option for strengthening climate change resilience, while contributing to food access, income, health, and environmental stability. To evaluate the evidence for such benefits, this systematic review identifies 22 peer-reviewed articles published between 2000 and 2019 which assess agroforestry’s contributions to food security in Indonesia, mostly in Java or Sumatra. Analysis of the studies indicate that traditional and commercial agroforestry contribute to food security in diverse ways: for example, traditional homegardens offer 20% more dietary diversity than commercial counterparts, while commercial homegardens may contribute up to five times more income. Agri-silviculture contributions fall along a timber versus non-timber forest product continuum that displays a similar tradeoff between diversity and income. Those systems with a commercial focus may receive 54% of their income from a single commodity crop such as coffee, while traditional systems allow greater access to plants with medicinal benefits. Nearly all agroforestry systems offered indirect benefits for food security, such as allowing more off-farm work than traditional agriculture and contributing to environmental stability: users of agroforestry were found by one study to collect 83% less fuelwood from natural forests. One study highlighted that agroforestry options have up to 98% greater net present value (for periods over 30 years) compared to slash and burn style agriculture. However, very few studies of Indonesian agroforestry focused explicitly on financial analysis and food security, indicating the need for further research. Given the similar situations faced by many Southeast Asia countries, our findings contribute to emerging trends throughout the region regarding the relationship between agroforestry and food security.

Traumatic brain injury-induced cerebral microbleeds in the elderly - Luca Toth; Andras Czigler; Peter Horvath; Balint Kornyei; Nikolett Szarka; Attila Schwarcz; Zoltan Ungvari; Andras Buki; Peter Toth (GeroScience, 2021)
Traumatic brain injury (TBI) was shown to lead to the development of cerebral microbleeds (CMBs), which are associated with long term cognitive decline and gait disturbances in patients. The elderly is one of the most vulnerable parts of the population to suffer TBI. Importantly, ageing is known to exacerbate microvascular fragility and to promote the formation of CMBs. In this overview, the effect of ageing is discussed on the development and characteristics of TBI-related CMBs, with special emphasis on CMBs associated with mild TBI. Four cases of TBI-related CMBs are described to illustrate the concept that ageing exacerbates the deleterious microvascular effects of TBI and that similar brain trauma may induce more CMBs in old patients than in young ones. Recommendations are made for future prospective studies to establish the mechanistic effects of ageing on the formation of CMBs after TBI, and to determine long-term consequences of CMBs on clinically relevant outcome measures including cognitive performance, gait and balance function.

Increases in hypertension-induced cerebral microhemorrhages exacerbate gait dysfunction in a mouse model of Alzheimer’s disease - Ádám Nyúl-Tóth; Stefano Tarantini; Tamas Kiss; Peter Toth; Veronica Galvan; Amber Tarantini; Andriy Yabluchanskiy; Anna Csiszar; Zoltan Ungvari (GeroScience, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

The Absence of PDR16 Gene Restricts the Overexpression of CaSNQ2 Gene in the Presence of Fluconazole in Candida albicans - Alexandra Bencova; Eduard Goffa; Marcela Morvova; Martin Valachovic; Peter Griač; Nora Toth Hervay; Yvetta Gbelska (Mycopathologia, 2020)

Cerebral venous congestion promotes blood-brain barrier disruption and neuroinflammation, impairing cognitive function in mice - Gabor A. Fulop; Chetan Ahire; Tamas Csipo; Stefano Tarantini; Tamas Kiss; Priya Balasubramanian; Andriy Yabluchanskiy; Eszter Farkas; Attila Toth; Ádám Nyúl-Tóth; Peter Toth; Anna Csiszar; et al. (GeroScience, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Vacuum evaporation and reverse osmosis treatment of process wastewaters containing surfactant material: COD reduction and water reuse - Eniko Haaz; Daniel Fozer; Tibor Nagy; Nora Valentinyi; Anita Andre; Judit Matyasi; Jozsef Balla; Peter Mizsey; Andras Jozsef Toth (Clean Technologies and Environmental Policy, 2019)

Repeated Valsalva maneuvers promote symptomatic manifestations of cerebral microhemorrhages: implications for the pathogenesis of vascular cognitive impairment in older adults - Zoltan Ungvari; Andriy Yabluchanskiy; Stefano Tarantini; Peter Toth; Angelia C. Kirkpatrick; Anna Csiszar; Calin I. Prodan (GeroScience, 2018)

Extensive comparison of biodiesel production alternatives with life cycle, PESTLE and multi-criteria decision analyses - Laszlo Racz; Daniel Fozer; Tibor Nagy; Andras Jozsef Toth; Eniko Haaz; Janka Ariella Tarjani; Anita Andre; Asmaa Selim; Nora Valentinyi; Laszlo Tamas Mika; Csaba Deak; Peter Mizsey (Clean Technologies and Environmental Policy, 2018)

Ergodicity and parameter estimates in auditory neural circuits - Peter G. Toth; Petr Marsalek; Ondrej Pokora (Biological Cybernetics, 2018)

Report on CIP-EAPR Workshop 2017 on Biocontrol and Biostimulants Agents for the Potato Crop, Held During the 20th EAPR Triennial Conference, Versailles, France, on Tuesday July 11, 2017 - André Devaux; Jean-Pierre Goffart; Peter Kromann; Ian Toth; Claude Bragard; Stefan Declerck (Potato Research, 2017)

Demonstration of impaired neurovascular coupling responses in TG2576 mouse model of Alzheimer’s disease using functional laser speckle contrast imaging - Stefano Tarantini; Gabor A. Fulop; Tamas Kiss; Eszter Farkas; Dániel Zölei-Szénási; Veronica Galvan; Peter Toth; Anna Csiszar; Zoltan Ungvari; Andriy Yabluchanskiy (GeroScience, 2017)

Peptide-Based Multicomponent Oligonucleotide Delivery Systems: Optimisation of Poly-l-lysine Dendrons for Plasmid DNA Delivery - Khairul A. Kamaruzaman; Peter M. Moyle; Istvan Toth (International Journal of Peptide Research and Therapeutics, 2017)

PACAP Is Protective in a Rat Model of Retinopathy of Prematurity - Timea Kvarik; Barbara Mammel; Dora Reglodi; Krisztina Kovacs; Dora Werling; Brigitta Bede; Alexandra Vaczy; Eszter Fabian; Gabor Toth; Peter Kiss; Andrea Tamas; Tibor Ertl; et al. (Journal of Molecular Neuroscience, 2016)

Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Induces Relaxations of Peripheral and Cerebral Arteries, which are Differentially Impaired by Aging - Zoltan Vamos; Ivan Ivic; Peter Cseplo; Gabor Toth; Andrea Tamas; Dora Reglodi; Akos Koller (Journal of Molecular Neuroscience, 2014)

PACAP Application Improves Functional Outcome of Chronic Retinal Ischemic Injury in Rats-Evidence From Electroretinographic Measurements - Bese Danyadi; Krisztina Szabadfi; Dora Reglodi; Agoston Mihalik; Tibor Danyadi; Zsolt Kovacs; Istvan Batai; Andrea Tamas; Peter Kiss; Gabor Toth; Robert Gabriel (Journal of Molecular Neuroscience, 2014)

Molecular Mechanisms Underlying the Nephroprotective Effects of PACAP in Diabetes - Eszter Banki; Krisztina Kovacs; Daniel Nagy; Tamas Juhasz; Peter Degrell; Katalin Csanaky; Peter Kiss; Gabor Jancso; Gabor Toth; Andrea Tamas; Dora Reglodi (Journal of Molecular Neuroscience, 2014)

A depth refugium from catastrophic coral bleaching prevents regional extinction - Tyler B. Smith; Peter W. Glynn; Juan L. Maté; Lauren T. Toth; Joanna Gyory (Ecology, 2014)
Species intolerant of changing climate might avoid extinction within refugia buffered from extreme conditions. Refugia have been observed in the fossil record but are not well documented or understood on ecological time scales. Using a 37‐year record from the eastern Pacific across the two most severe El Niño events on record (1982–1983 and 1997–1998) we show how an exceptionally thermally sensitive reef‐building hydrocoral, Millepora intricata , twice survived catastrophic bleaching in a deeper‐water refuge (>11 m depth). During both events, M. intricata was extirpated across its range in shallow water, but showed recovery within several years, while two other hydrocorals without deep‐water populations were driven to regional extinction. Evidence from the subfossil record in the same area showed shallow‐water persistence of abundant M. intricata populations from 5000 years ago, through severe El Niño–Southern Oscillation cycles, suggesting a potential depth refugium on a millennial timescale. Our data confirm the deep refuge hypothesis for corals under thermal stress.

Cardiac glutaminolysis: a maladaptive cancer metabolism pathway in the right ventricle in pulmonary hypertension - Lin Piao; Yong-Hu Fang; Kishan Parikh; John J. Ryan; Peter T. Toth; Stephen L. Archer (Journal of Molecular Medicine, 2013)

FOXO1-mediated upregulation of pyruvate dehydrogenase kinase-4 (PDK4) decreases glucose oxidation and impairs right ventricular function in pulmonary hypertension: therapeutic benefits of dichloroacetate - Lin Piao; Vaninder K. Sidhu; Yong-Hu Fang; John J. Ryan; Kishan S. Parikh; Zhigang Hong; Peter T. Toth; Erik Morrow; Shelby Kutty; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Identification of genes in the VirR regulon of Pectobacterium atrosepticum and characterization of their roles in quorum sensing‐dependent virulence - Rita Monson; Tom Burr; Timothy Carlton; Hui Liu; Peter Hedley; Ian Toth; George P.C. Salmond (Environmental Microbiology, 2013)
Summary In the economically important phytopathogen, Pectobacterium atrosepticum , expression of plant cell wall degrading enzymes and other virulence determinants is controlled in a cell density‐dependent fashion, termed quorum sensing (QS). Canonical QS systems in Gram‐negative bacteria contain a LuxI‐type protein, synthesizing a signalling molecule, and a LuxR‐type regulator, responding to the signalling molecule above threshold concentrations. In P. atrosepticum , the central LuxR‐type repressor of virulence, VirR, has been identified and its impacts on virulence characterized. Here we define the broader VirR regulon using chromatin immunoprecipitation (ChIP) and in planta microarrays. Ninety‐four direct VirR targets were identified by ChIP microarrays and a consensus VirR binding site was determined. Purified VirR was used in DNA gel shift assays on target promoters and VirR : promoter binding was disrupted by exogenous addition of the signalling molecule, N ‐(3‐oxohexanoyl)‐ l ‐homoserine lactone (OHHL). VirR autorepressed, and directly activated the transcription of rsmA in the absence of OHHL. Finally, we showed that VirR directly regulated the production of siderophores and controlled swimming motility. This is the first report characterizing the direct targets of VirR and provides clear evidence that this LuxR‐type protein can act in vivo as both an activator and repressor of transcription in the absence of its cognate signalling molecule.

Therapeutic inhibition of fatty acid oxidation in right ventricular hypertrophy: exploiting Randle’s cycle - Yong-Hu Fang; Lin Piao; Zhigang Hong; Peter T. Toth; Glenn Marsboom; Peter Bache-Wiig; Jalees Rehman; Stephen L. Archer (Journal of Molecular Medicine, 2012)

Effects of PACAP in UV-A Radiation-Induced Retinal Degeneration Models in Rats - Tamas Atlasz; Krisztina Szabadfi; Peter Kiss; Zsuzsanna Marton; Monika Griecs; Levente Hamza; Valeria Gaal; Zsolt Biro; Andrea Tamas; Gabor Hild; Miklos Nyitrai; Gabor Toth; et al. (Journal of Molecular Neuroscience, 2011)

Effects of PACAP on Mitochondrial Apoptotic Pathways and Cytokine Expression in Rats Subjected to Renal Ischemia/Reperfusion - Gabriella Horvath; Boglarka Racz; Dora Reglodi; Krisztina Kovacs; Peter Kiss; Ferenc Gallyas; Zita Bognar; Aliz Szabo; Tamas Magyarlaki; Eszter Laszlo; Andrea Lubics; Andrea Tamas; et al. (Journal of Molecular Neuroscience, 2010)

The inhibition of pyruvate dehydrogenase kinase improves impaired cardiac function and electrical remodeling in two models of right ventricular hypertrophy: resuscitating the hibernating right ventricle - Lin Piao; Yong-Hu Fang; Virgilio J. J. Cadete; Christian Wietholt; Dalia Urboniene; Peter T. Toth; Glenn Marsboom; Hannah J. Zhang; Idith Haber; Jalees Rehman; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2010)

Effects of PACAP on the Circadian Changes of Signaling Pathways in Chicken Pinealocytes - Boglarka Racz; Gabriella Horvath; Nandor Faluhelyi; Andras D. Nagy; Andrea Tamas; Peter Kiss; Ferenc Gallyas; Gabor Toth; Balazs Gaszner; Valer Csernus; Dora Reglodi (Journal of Molecular Neuroscience, 2008)

Effects of PACAP on Survival and Renal Morphology in Rats Subjected to Renal Ischemia/Reperfusion - Peter Szakaly; Peter Kiss; Andrea Lubics; Tamas Magyarlaki; Andrea Tamas; Boglarka Racz; Istvan Lengvari; Gabor Toth; Dora Reglodi (Journal of Molecular Neuroscience, 2008)

PACAP Has Anti-apoptotic Effect in the Salivary Gland of an Invertebrate Species, Helix pomatia - Zsolt Pirger; Jozsef Nemeth; Laszlo Hiripi; Gabor Toth; Peter Kiss; Andrea Lubics; Andrea Tamas; Laszlo Hernadi; Tibor Kiss; Dora Reglodi (Journal of Molecular Neuroscience, 2008)

Investigation of the Effects of PACAP on the Composition of Tear and Endolymph Proteins - Valeria Gaal; Laszlo Mark; Peter Kiss; Ildiko Kustos; Andrea Tamas; Bela Kocsis; Andrea Lubics; Viktoria Nemeth; Adrienn Nemeth; Laszlo Lujber; Jozsef Pytel; Gabor Toth; et al. (Journal of Molecular Neuroscience, 2008)

Is Xysticus kochi (Araneae: Thomisidae) an efficient indigenous biocontrol agent of Frankliniella occidentalis (Thysanoptera: Thripidae)? - Peter Zrubecz; Ferenc Toth; Attila Nagy (BioControl, 2008)

Is Xysticus kochi (Araneae: Thomisidae) an efficient indigenous biocontrol agent of Frankliniella occidentalis (Thysanoptera: Thripidae)? - Peter Zrubecz; Ferenc Toth; Attila Nagy (BioControl, 2008)

Differential modulation of agonist and antagonist structure activity relations for rat TRPV1 by cyclosporin A and other protein phosphatase inhibitors - Larry V. Pearce; Attila Toth; HyungChul Ryu; Dong Wook Kang; Hyun-Kyung Choi; Mi-Kyoung Jin; Jeewoo Lee; Peter M. Blumberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Diurnal Alterations of Brain Electrical Activity in Healthy Adults: A LORETA Study - Marton Toth; Attila Kiss; Peter Kosztolanyi; Istvan Kondakor (Brain Topography, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Synthesis and Immunological Evaluation of M Protein Targeted Tetra-Valent and Tri-Valent Group A Streptococcal Vaccine Candidates Based on the Lipid-Core Peptide System - Peter Michael Moyle; Colleen Olive; Levente Karpati; Nadia Barozzi; Mei-Fong Ho; Joanne Dyer; Hsien Kuo Sun; Michael Good; Istvan Toth (International Journal of Peptide Research and Therapeutics, 2006)

Climate Change, Flow Regulation and Land-Use Effects on the Hydrology of the Peace-Athabasca-Slave System; Findings from the Northern Rivers Ecosystem Initiative - T. D. Prowse; S. Beltaos; J. T. Gardner; J. J. Gibson; R. J. Granger; R. Leconte; D. L. Peters; A. Pietroniro; L. A. Romolo; B. Toth (Environmental Monitoring and Assessment, 2006)

Practical Method for Analysis of Immiscible Displacement in Laboratory Core Tests - Janos Toth; Tibor Bodi; Peter Szucs; Faruk Civan (Transport in Porous Media, 1998)